2(2+b)+(2b)=900

Simple and best practice solution for 2(2+b)+(2b)=900 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2+b)+(2b)=900 equation:


Simplifying
2(2 + b) + (2b) = 900
(2 * 2 + b * 2) + (2b) = 900
(4 + 2b) + (2b) = 900

Combine like terms: 2b + (2b) = 4b
4 + 4b = 900

Solving
4 + 4b = 900

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 4b = 900 + -4

Combine like terms: 4 + -4 = 0
0 + 4b = 900 + -4
4b = 900 + -4

Combine like terms: 900 + -4 = 896
4b = 896

Divide each side by '4'.
b = 224

Simplifying
b = 224

See similar equations:

| 5x^2-23z+12=0 | | 4-9=4x | | 5y+9wheny=6 | | 0=15m^2-10m-25 | | 1.10=2x+1 | | 2(y-3)=34 | | 4-8=4x-1 | | y=15m^2-10m-25 | | -12r^2+4=13r | | in(8x)=5.5 | | 3(5-2)=y | | -81-6x=-18+3x | | (5z+6)(3-z)=0 | | -7(x+3)=-16-7a | | 3gh-4h= | | -(3-4m)=7-6m | | 2b-18= | | 8(2(2)+4)-3(3(2)-6)= | | (5x-2)(-5x-4)= | | 3(6-1)=11p-45 | | A^2(b-1)-25(b-1)= | | 2(-5)+7(-25)-9(-5)+21(-50)+5(-5)= | | (k+1)x^2+(k+1)y^2+2kx+2ky+2y+4k+3=0 | | .25x-5+171=x | | 20/12=50/x | | 3(-5)(2)+6(-5)+-5(3(2)-6)= | | 2x+3x+(2+6)=8 | | 7x-2=4x-2 | | y=-2x+16x-24 | | ln(5x-2)-ln(x+3)=2 | | 5(2+p)=17.5 | | 5x+45-89=-90+41 |

Equations solver categories